The level of teaching practices among Arabic language teachers for the intermediate stage in light of the sustainable development goals in Makkah Al-Mukarramah - Al-Dosari, Mashael Saleh; Al-Zahrani, Noura Abdullah (Journal of Curriculum and Teaching Methodology, 2024)
This research aimed to identify the level of teaching practices among Arabic language middle school teachers considering the sustainable development goals in Mecca. The descriptive approach was used, and the research sample consisted of (35) Arabic language middle school teachers for the year (1445 AH). The two researchers provided a list of teaching practices that achieve the goals of sustainable development in middle schools, and in its final form it consisted of three main axes: teaching practices for the social goals of sustainable development, teaching practices for the environmental goals of sustainable development, and teaching practices for the economic goals of sustainable development. with that being said the “observation card” research tool, and the results showed that the general average of the teaching practices employed by Arabic language teachers in middle schools to achieve the sustainable development goals in general was (1.81) which is the average that indicates that the teaching practices employed by female Arabic language teachers in the middle school to achieve the sustainable development goals was moderate in general, as teaching practices for social development goals came in first place with a percentage of (2.21), then teaching practices for economic development goals with a percentage of (1.88), then teaching practices for environmental development goals with a percentage of (1.34). The researchers came out with many recommendations, including programs to prepare and train Arabic language teachers on the necessary teaching practices considering the sustainable development goals, as well as developing a guide for teachers that includes activities and practices that achieve the sustainable development goals in Arabic language classes.